Lymphoid immunohistochemistry of macaque primates. - Ormerod, L D (1988)
The immunohistochemical localizations of 53 monoclonal antibodies with specificities expressed in human lymphoid tissue were investigated on lymph node tissues from Macaca mulatta, M. speciosa, and M. fascicularis using immunoperoxidase techniques. Thirty antibodies showed comparative cross-reactivity. The micro-anatomic distribution of these antigens was closely homologous to that observed in man and antigen densities appeared to be similar. A useful monoclonal antibody panel for immunopathological investigations in macaques was, thereby, defined. Of several pan-T antibodies studied, only OKT11(CD2) showed cross-reactivity. A detailed analysis of the immunocyto-architecture of five rhesus lymph nodes was undertaken. Automated flow cytometry of M. mulatta and M. speciosa peripheral blood showed a broadly similar pattern to man.